Back to Normal: Direct Evidence of the Cretan Detachment as a North‐Directed Normal Fault During the Miocene. Issue 8 (17th August 2019) - Grasemann, B.; Schneider, D. A.; Rogowitz, A.
Abstract: The Cretan Detachment represents a major tectonic contact between an Alpine high‐pressure Lower Nappe System in the footwall and an Alpine unmetamorphosed Upper Nappe System in the hanging wall. Interestingly, the kinematics and the tectonic nature of this contact is still highly controversial and has been interpreted either as a top‐to‐the S thrust or as a normal fault with top‐to‐the N and/or top‐to‐the S displacement sense. Whereas some models suggest exhumation of the high‐pressure rocks synchronous with out‐of‐sequence thrusting or Himalayan‐type extrusion tectonics, other models propose that Crete represents a metamorphic core complex that exhumed below the extensional Cretan Detachment. In this work, we show that the Cretan Detachment in eastern Crete is an up to 100‐m‐thick cataclastic low‐angle fault zone, which localized below the Tripolitza Unit (Upper Nappe System) within the upper part of the Upper Violet Slates (top of Lower Nappe System) cutting downsection to lower structural levels. The unequivocal kinematic indicators in this fault zone clearly suggest a top‐to‐the N displacement of the hanging wall. New low‐temperature geochronological data and numerical modeling suggest rapid cooling of the rocks in the footwall of the Cretan Detachment at circa 15 Ma. Top‐to‐the S ductile shear sense toward lower structural level in the Lower Nappe System support the idea that the Cretan Detachment facilitated the exhumation of the high‐pressure rocks in an extrusion tectonic setting. Therefore, in the early to middle Miocene, subduction‐related extrusion in Crete was simultaneously active with back‐arc extension‐related metamorphic core formation in the Cyclades. Key Points: Cretan Detachment is an extrusion‐related low‐angle normal fault that operated mainly under brittle conditions A suite of clear shear sense indicators from brittle fault rocks demonstrates that the kinematic of the Cretan Detachments is top‐to‐the N Low‐temperature geochronology and numerical modeling indicates that the Cretan Detachment was active in the Middle Miocene